Implementation of the Maternal and Neonatal Tetanus Elimination (MNTE) Program at the Banjarmasin Health Center - Susanti Suhartati; Lisda Handayani (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2021)
BackgroundIncreasing the coverage of routine TT immunization that is high and evenly distributed is an effort to prevent tetanus toxoid. One of the ways to increase the coverage of routine TT immunization is the implementation of the Maternal and Neonatal Tetanus Elimination (MNTE) program. The Maternal and Neonatal Tetanus Elimination (MNTE) program is implemented by all Puskesmas as the first service for Tetanus Toxoid immunization.  ObjectiveDescribe the causes of low TT coverage at the Banjarmasin City Health Center and describe the obstacles faced in the process of implementing the Maternal and Neonatal Tetanus Elimination (MNTE) program in Banjarmasin City MethodThis research is a quantitative descriptive study using Cross Sectional. With Acidental Sampling with a total of 150 respondents consisting of pregnant women and 25 midwives at the Banjarmasin Health Center ResultsAre still 28 people or 18.7% of pregnant women who have never been able to use TT, there are only 6 pregnant women or 4% of pregnant women with TT 4 status and there are 54 pregnant women or 36% of women. pregnant with TT 1 status. A total of 78 people or 52% have less knowledge of TT techniques. As many as 88 people or 58.6% have a negative attitude towards TT, as much as 59.4% of pregnant women stated that the role of officers is still lacking in explaining the TT technique. Service documentation is only centered on service providers, documentation is not clearly accessible or readable by service recipients. low parity need more effort in utilizing TT. Lack of information and knowledge causes there are still pregnant women with negative attitudes towards exercise. ConclusionMNTE services at the Banjarmasin Health Center require increased promotion efforts, and media documentation that can be owned by women of childbearing age to find out TT and can fulfill TT status up to TT 5. KeywordsImmunization TT, Tetanus, MNTE Latar BelakangPeningkatan cakupan imunisasi rutin TT yang tinggi dan merata adalah upaya pencegahan tetanus toxoid. Meningkatkan Cakupan imunisasi rutin TT salah satunya dengan telah penerapan program Maternal and Neonatal Tetanus Elimination (MNTE). Program Maternal and Neonatal Tetanus Elimination (MNTE) dilaksanakan oleh semua Puskesmas sebagai pelayanan pertama imunisasi Tetanus Toksoid. TujuanMendeskripsikan penyebab rendahnya Cakupan TT di Puskesmas Kota Banjarmasin dan mendeskripsikan kendala yang di hadapi dalam proses pelaksaan program Maternal and Neonatal Tetanus Elimination (MNTE) di Kota BanjarmasinMetodePenelitian ini adalah penelitian deskriptif kuantitasif dengan menggunakan Cross Sectional. Dengan Acidental Sampling dengan total responden sebanyak 150 responden yang terdiri dari ibu hamil dan 25 bidan di puskesmas kota BanjarmasinHasilStatus imunisasi sejumlah 28 orang atau 18,7% ibu hamil belum pernah mendapatkan imunisasi TT hanya terdapat 6 orang ibu hamil atau 4% ibu hamil dengan status TT 4 dan terdapat 54 orang ibu hamil atau 36% ibu hamil dengan status TT 1.  Sebanyak 78 orang atau 52% memiliki pengetahuan kurang terhadap imunisasi TT. Sebesar 88 orang atau 58,6% memiliki sikap negative terhadap imunisasi TT, sebesar 59,4% ibu hamil menyatakan peran petugas masih kurang dalam penjelasan tentang imunisasi TT. Dokumentasi layanan imunisasi hanya berpusat pada pemberi pelayanan. Kurangnya informasi dan pengetahuan menyebabkan masih terdapat ibu hamil dengan sikap negative terhadap imunisasi.KesimpulanPelayanan MNTE di Puskesmas membutuhkan peningkatan upaya promosi, dan media dokumentasi yang dapat dimiliki oleh Wanita Usia Subur untuk mengetahui status TT dan dapat terpenuhi status TT hingga TT 5.Kata Kunci :Imunisasi TT, Tetanus, MNTE